The Care & Keeping of You - Schaefer, Valorie Lee; Nang Chan Yeema (Middleton, WI USA Pleasant Company Publications, 1998)
A preteen girl's guide to basic health and hygiene - from braces to bras, pimples to periods, hair care to healthy eating.
Keywords: Adult Nonfiction